UPAYA PENINGATAN PENGETAHUAN TENTANG PEMANFAATAN DAUN KUBIS SEBAGAI UPAYA DALAM MENGURANGI BENGKAK PAYUDARA PADA IBU NIFAS - Yopi Suryatim Pratiwi; Sri Handayani; Dian Soekmawaty Riezqy Ariendha; Sephia Nur Alfiani (Stikes Yarsi Mataram, 2022)
Breast engorgement is the blockage of milk due to narrowing of the lactiferousducts or by glands that are not emptied completely. Breast engorgement is oftenexperienced by postpartum mothers. Several interventions that can be done toreduce breast swelling are pharmacological and non-pharmacological. Cabbageleaf compress is one of the non-pharmacological treatments that can be used asan effort to reduce breast swelling. Based on this, it is necessary to conducthealth education about the use of cabbage leaves as an effort to reduce breastswelling in postpartum mothers. This health education activity was carried out onAugust 14, 2020 in Dasan Baru, Sukarara Village, Jonggat District, CentralLombok Regency. Posttest results showed that postpartum mothers experiencedan increase in knowledge after being given health education about the use of cabbage leaves as an effort to reduce breast swelling. After the service activities,postpartum mothers are expected to be able to use cabbage leaves as an effortto reduce swelling in the breasts of postpartum mothers.